Regulation of stem and progenitor cells in the adrenal cortex. (October 2019) - Finco, Isabella; Mohan, Dipika R.; Hammer, Gary D.; Lerario, Antonio Marcondes
Abstract: The adrenal cortex is an endocrine organ comprised of three histological zones, the outermost zona glomerulosa, the intermediate zona fasciculata, and the innermost zona reticularis. High plasticity of the adrenal gland is supported by pools of stem and progenitor cells that are deployed to sustain physiological and homeostatic demands. In recent decades, exciting new discoveries elucidating the identity, function, and fate of these cell populations have emerged. In this review, we describe paracrine and endocrine signaling loops that are crucial for adrenal biology, focusing on recent studies unpacking the enigmatic nature of adrenal stem and progenitor cell populations.